2021
DOI: 10.7717/peerj.11044
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly ofAmorpha fruticosaL. transcriptome in response to drought stress provides insight into the tolerance mechanisms

Abstract: Background Amorpha fruticosa L. is a deciduous shrub that is native to North America and has been introduced to China as an ornamental plant. In order to clarify the drought resistance characteristics of Amorpha fruticosa L. and excavate the related genes involved in drought resistance regulation pathway, the mechanism of drought resistance stress of Amorpha fruticosa L. was revealed by the changes of transcriptome of Amorpha fruticosa L. under drought stress.Through the changes of the transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The metabolic process may contribute to the cold tolerance in the northward invasion of Alternanthera philoxeroides [105]. The oxidation-reduction process is involved in the drought stress response in Amorpha fruticosa seedlings [106] and in the adaptation to hypoxia and low temperatures in Kandelia obovata [107]. Effective responses to environmental changes or stress stimuli are beneficial for the colonization and adaptation of invasive plants in nonindigenous areas.…”
Section: Role Of Adaptive Genes In M Micranthamentioning
confidence: 99%
“…The metabolic process may contribute to the cold tolerance in the northward invasion of Alternanthera philoxeroides [105]. The oxidation-reduction process is involved in the drought stress response in Amorpha fruticosa seedlings [106] and in the adaptation to hypoxia and low temperatures in Kandelia obovata [107]. Effective responses to environmental changes or stress stimuli are beneficial for the colonization and adaptation of invasive plants in nonindigenous areas.…”
Section: Role Of Adaptive Genes In M Micranthamentioning
confidence: 99%
“…Four-week-sized seedlings of A. fruticosa were grown hydroponically in a 20% PEG 6000 (polyethylene glycol 6,000) solution for 72 h. Whole seedlings were sampled separately from the stressed and unstressed treatments, rapidly frozen in liquid nitrogen, and stored in a − 80°C refrigerator. After transcriptome sequencing results were obtained ( Sun et al, 2021 ), co-expression networks of genes were constructed using the WGCNA (Weighted Gene Co-expression Network Analysis) R package.…”
Section: Methodsmentioning
confidence: 99%
“…NAC-like transcription factors are one of the largest families of transcription factors specific to plants, and they play an important role in response to various abiotic stresses, such as salt, drought, and damage. In herbaceous plants such as Arabidopsis thaliana ( Mahmood et al, 2019 ), rice ( Li, 2014 ), alfalfa ( Shen et al, 2014 ), and land cotton ( Shah, 2013 ), NAC transcription factors were found to be upregulated in response to abiotic stresses, and in woody plants such as tamarisk ( Lu et al, 2019 ) and poplar ( Wang et al, 2015 ), PEG-6000 mimics drought stress; the transcriptome detected upregulation of NAC-like transcription factors in response to drought-induced differences in gene expression ( Sun et al, 2021 ). The NAC family has been found to function in a variety of processes, including apical meristem organization ( Takada et al, 2001 ), flower development ( Sablowski and Meyerowitz, 1998 ), cell division ( Kim et al, 2006 ), leaf senescence ( Breeze et al, 2011 ), secondary wall formation ( Zhong et al, 2010 ), and biotic and abiotic stress responses ( Olsen et al, 2005 ; Christianson et al, 2010 ; Tran et al, 2010 ; Nakashima et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although studies on the drought resistance of A. fruticosa WRKY TFs are limited, transcriptome sequencing analysis of A. fruticosa has shown that the AfWRKY20 gene is upregulated in response to drought-induced expression [44]. In this study, the AfWRKY20 gene was cloned from the transcriptome sequencing of A. fruticosa under drought stress using RT-PCR technology.…”
Section: Introductionmentioning
confidence: 99%